2023
DOI: 10.1093/jpids/piad045
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Incidence of First RSV Hospitalization in Children Born in Ontario, Canada

Abstract: Background Respiratory syncytial virus (RSV) contributes significantly to morbidity in children, placing substantial burdens on health systems, thus RSV vaccine development and program implementation are a public health priority. More data on burden are needed by policymakers to identify priority populations and formulate prevention strategies as vaccines are developed and licensed. Materials/methods Using health administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Buchan et al reported 5% ICU admission for healthy children younger than five years, increasing to 10% with comorbidities (( 18 )). In their 2023 study, ICU admission reached 8.1% among RSV-hospitalized children under five, with higher rates for premature births (( 13 )). In one Canadian study, ICU admission was more common with RSV compared to influenza (( 19 )).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Buchan et al reported 5% ICU admission for healthy children younger than five years, increasing to 10% with comorbidities (( 18 )). In their 2023 study, ICU admission reached 8.1% among RSV-hospitalized children under five, with higher rates for premature births (( 13 )). In one Canadian study, ICU admission was more common with RSV compared to influenza (( 19 )).…”
Section: Resultsmentioning
confidence: 99%
“…An Ontario study by Pisesky et al reported RSV hospitalization rates of 10.2 per 1,000 children younger than one year and 4.8 per 1,000 in children one to three years of age (( 12 )). Buchan et al ’s Ontario cohort study revealed varying RSV hospitalization rates across age groups, with the highest in one-month-olds (n=29.55 per 1,000) and declining with age, with rates highest among children born at younger gestational ages (( 13 )). Over five respiratory seasons from 2018 to 2023 in Yukon, there were 27 severe RSV cases (non-ICU hospitalizations, ICU admissions and deaths), of which 18 were non-ICU hospitalizations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3639 Due to this monthly change in viral risk combined with granularity in palivizumab and nirsevimab’s current indications for use in Canada, we strived to utilize monthly data inputs from Canada in our model. Given the lack of such data and the common seasonality of RSV and similar incidence in infants in Canada and the United States, 40,41 we opted to extrapolate US-based health outcomes and cost inputs and modify them using average Canadian values. Incorporating monthly data inputs was deemed critical to the ability of our model to estimate the clinical and cost impact of nirsevimab vs. standard care.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of RSV-associated hospitalizations by gestational age at birth were derived from a systematic review (17). Case-fatality and age-specific background mortality rates were obtained from the literature (3, 18, 19). The case-fatality rate was adjusted to account for background mortality.…”
Section: Methodsmentioning
confidence: 99%